Equal justice fair legal systems in an unfair world - Wilmot-Smith, Frederick, 1986- (Harvard University Press, 2019)
It cannot be fair that wealthy people enjoy better legal outcomes. That is why Frederick Wilmot-Smith argues that justice requires equal access to legal resources. At his most radical, he urges us to rethink the centrality of the market to legal systems, so that those without means can secure justice and the rich cannot escape the law's demands